Thought Leadership on the Revolutionary Developments in Organizations - Brady, Ursula; Kuria, Kathy; Bell, Reginald L. (American Journal of Management, 2025)
This study investigated thought leadership concerning organizational growth strategies. Internal Thought Leaders (ITL) and External Thought Leaders (ETL) we identified in the literature to be directly related to achieving revolutionary developments in organizations (RDO). We found that ITL are better suited for setting goals, aligning resources, and fostering innovations; on the other hand, ETL were better suited to advance organizational reputation. We explicate a progressive thought leadership framework that works best to sustain organizational growth strategies. This integrative approach can impact ethical decision-making, leadership styles, operation efficiencies and return on investments if done properly. Because thought leadership influences a collective mindset among workers, we were able to make several recommendations for managers seeking to influence their organizational growth strategies.